A comparison of antioxidant activity of Korean White and Red Ginsengs on H₂O₂-induced oxidative stress in HepG2 hepatoma cells - Sohn, Sang-Hyun; Kim, Si-Kwan; Kim, Young-Ock; Kim, Hyung-Don; Shin, Yu-Su; Yang, Seung-Ok; Kim, Seung-Yu; Lee, Sang-Won (Journal of ginseng research, 2013)
The aim of this study was to determine and compare the preventive effect of Korean White Ginseng and Red Ginseng on oxidative stress in H2O2-treated HepG2 cells. The roots of ginseng were extracted with 70% methanol and partitioned with butanol to obtain saponin fractions, which have been known as bioactive constituents of ginseng. 2',7'-Dichlorofluorescein diacetate (DCF-DA) assay and malondialdehyde (MDA) content were measured for evaluating intracellular reactive oxygen species (ROS) generation. Also, mRNA expressions and activities of antioxidant enzymes were analyzed to determine the antioxidant activity of saponin or non-saponin fractions of ginsengs. According to DCF-DA assay, H2O2-induced MDA release and ROS generation were significantly reduced by treatment with saponin fractions of white and red ginseng roots. Also, saponin fractions increased effectively intracellular antioxidant enzyme activities including catalase, glutathione peroxidase and superoxide dismutase in H2O2- treated HepG2 hepatoma cells. In general, red ginseng was more effective than white ginseng for reducing oxidative stress. These results indicate that administration of red ginseng may certainly contribute relatively stronger than white ginseng to prevent from damaging liver function by oxidative stress.